(untitled) (Biological Sciences - PJSIR, 2024)
The poultry market is troubled by Salmonellosis infections which has a large negative impact due to morbidity and decreased productivity. Salmonella pullorum causes a disease named Salmonellosis which affects the poultry industries and has long been a significant obstacle to the development of nations. Due to the occurrence of resistance to most of the antibiotics in the poultry, treatment of infection now becomes difficult and challenging. So, alternative therapy is needed to reduce the burden of bacterial load and to treat the infection. The main objectives of this study were to isolate Salmonella pullorum from the layer poultry birds with to check antibiotic resistance of Salmonella pullorum and to isolate lytic phages against Salmonella pullorum. Poultry fecal samples were collected from poultry farms in different areas. For isolation and purification of Salmonella pullorum, Salmonella Shigella agar (SS-agar) was used. Black centered colonies were observed on SS agar and non-lactose fermenter on MacConkey’s agar. For the confirmation of bacterial isolates, gram staining yielded pink- red rods as observed microscopically. For citrate utilization isolates also +ve test, catalase production and methyl red reaction and negative for VP and indole reaction. The disk diffusion method on Mueller Hinton was performed to check the susceptibility pattern of Salmonella pullorum. Bacterium showed resistance to amoxicillin followed by tetracycline and ceftazidime, while sensitive to chloramphenicol and kanamycin. Sewage water was collected for the isolation of phages from different sewage lines of poultry farms. Bacteriophages against Salmonella pullorum were isolated through agar overlay method. Clear plaques were observed on petri plates.